MULTIPLIER EFFECT BUSINESS OF PATIN FISH CULTURE (Pangasius sutchi) IN KOTO MESJID VILLAGE SUBDISTRICT XIII KOTO KAMPAR REGENCY KAMPAR PROVINCE RIAU - Zulkarnaen, Febri; Yulinda, Eni; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT    This research was conducted on November 18, 2018 until December06, 2018 in Koto Mesjid Village, Subdistrict XIIIKoto Kampar, Kampar Regency, Riau Province. The purpose of this study is to identify economic activities that are growing as a result of the presence of Patin fish culture(Pangasius sutchi) and to find out the multiplier effect of the existence of Patin fish culture (Pangasius sutchi). The research method used is the Survey Method conducted directly by observing the research object. The technique of determining respondents used is based on Purposive Sampling with the number of respondents as many as 38 owners of Patin fish culture businesses, 2 Patin fish hatchery businesses, 2 processed fish business actors, 4 feed making businesses and 4 workers from each unit.The results of the study show that economic activities that have grown as a result of the existence of three Patin (Pangasius sutchi) cultivation business, namely: the business of fish stocking, feed making business, and processed fish business. l The large economic impact of Patin fish culture is the estimation of the velocity of money with the number of 835 ponds for one business production reaching IDR.50.007.000.000 and the turnover of money for one year reaching IDR.100.014.000.000. While the multiplier effect of the existence of Patin fish culture (Pangasius sutchi) has provided an economic impact seen from the direct impact, indirect impacts and further impacts. The value of the Type II Ratio Income Multiplier is 1.0. This shows that the Patin fish culture business has had an economic impact on the community.Keywords: Multiplier Effect, Cultivation Business, Patin Fish